Lentivirus de pequenos ruminantes: caracterização genética e antigênica de isolados de caprinos e ovinos do Brasil - Gissandra Farias Braz (2013)
With the goal to isolate and characterize by phylogenetic and antigenic analysis the small ruminant lentiviruses (SRLV), choroid plexus; MSC, PBMC and BAL samples from 44 goats and 1882 goat and 67 sheep serums from Northeast, Southeast and South of the Brazil were collected between 2009 at 2011. Proviral DNA from 32 SRLV isolates and from blood (6 goats and 2 sheep) were amplified by nested PCR PCR in two fragments spanning either the V1V2 (394pb) or V4V5 (608pb) of env region, and one gag fragment (990pb) containing partial MA and entire CA coding sequence, followed by nucleotide sequencing. The antigenic response of sera ware evaluated against multiepitope recombinant antigens with immunodominant domains of structural proteins (CA, MA, SU, based on the A13 and B1 subtypes). LVPR were isolated from 42 goats, and showed no association between LVPR isolation and clinical signs, age, breed or production type. LVPR genetic and antigenic characterization showed mainly the B1 subtype in dairy goats, despite having also been found in sheep. Additionally, the genotype A was found in goats. LVPR classification of sheep in B and goat in A-groups evidenced the MVV and CAEV interspecies transmission in Brazil. Amino acid analysis (V4/V5) identified coinfection or recombination occurring in goats, among which two discordant virus clusters corresponding to group A and B group, demonstrating that this goats was dually infected, while another virus showed a new motive inserted in the protein surface immunogenic region (V4 domain). These results demonstrated the genetic and antigenic diversity of Brazilian SRLV strains circulating in country, and confirm the necessity to consider all the viral genotypes in antigens used to serological tests, in order to prevent misdiagnosis and increase the accuracy of these in the SRLV controls programs